2019
DOI: 10.1038/s41536-019-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human embryonic stem cell-derived retinal pigment epithelial cells (MA09-hRPE) in macular degeneration

Abstract: The use of human embryonic stem cell (hESC)-derived Retinal Pigment Epithelium (RPE) transplants has advanced dramatically in different forms for clinical application in macular degeneration. This review focuses on the first generation of hESC-RPE cell line, named as “MA09-hRPE” by Astellas Institute of Regenerative Medicine (AIRM), and its therapeutic application in human, which evaluated the safety and efficacy of MA09-hRPE cell line transplanted in patients with macular degeneration. This project marks the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Differentiated RPE cells are post-mitotic and fully committed to the RPE lineage, in large part due to their cell–cell contact inhibition [53] , [54] . The expression of the proliferation marker MKI67 and of other genes associated with proliferation ( TOP2A , TPX2 , PTTG1 , PCLAF , and RRM2 ) was examined to assess whether some progenitor populations remain with proliferative potentials, and whether these vary over time in culture.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiated RPE cells are post-mitotic and fully committed to the RPE lineage, in large part due to their cell–cell contact inhibition [53] , [54] . The expression of the proliferation marker MKI67 and of other genes associated with proliferation ( TOP2A , TPX2 , PTTG1 , PCLAF , and RRM2 ) was examined to assess whether some progenitor populations remain with proliferative potentials, and whether these vary over time in culture.…”
Section: Resultsmentioning
confidence: 99%
“…MA09-hRPE (Astellas Pharma) is hESC-derived Retinal Pigment Epithelium (hESC-RPE). The phases 1/2 clinical trial results confirmed that hESC-derived cells could serve as a potentially safe new source for regenerative medicine [21][22][23].…”
Section: Cell-based Therapiesmentioning
confidence: 78%
“…The interactions between RPE and cells of the neuroretina is crucial for optimal functioning of either cell type. Derivation of pure single cell type populations does not necessarily ensure complete functionality [ 43 ]. We propose that a cocktail of cells might better imitate the in vivo interactions.…”
Section: Discussionmentioning
confidence: 99%